2002
DOI: 10.1021/ol017003g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oligonucleotides Containing Thiazole and Thiazole N-Oxide Nucleobases

Abstract: [reaction: see text] The thiazole C-nucleoside analogue was synthesized by the Hantzsch cyclization method to form the thiazole ring and was then converted to the thiazole N-oxide C-nucleoside analogue by peracid oxidation of the heterocycle nitrogen. Incorporation of the thiazole and thiazole N-oxide phosphoramidites into DNA was successful though significant deoxygenation of the N-oxide occurred during DNA assembly. The mechanism proposed for the reduction of the thiazole N-oxide to thiazole involves the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The N -oxide function was found to be very stable toward triethyl phosphite for at least 24 h. Interestingly, the reaction of 5 with diphenyl phosphite led to the deoxygenation of the N -oxide moiety ( t 1/2 = 4 h). In connection with our study, Hammer has recently reported the facile reduction of a 2‘-deoxynucleoside analog using a thiazole N -oxide nucleobase with phosphitylating reagents …”
Section: Resultsmentioning
confidence: 66%
“…The N -oxide function was found to be very stable toward triethyl phosphite for at least 24 h. Interestingly, the reaction of 5 with diphenyl phosphite led to the deoxygenation of the N -oxide moiety ( t 1/2 = 4 h). In connection with our study, Hammer has recently reported the facile reduction of a 2‘-deoxynucleoside analog using a thiazole N -oxide nucleobase with phosphitylating reagents …”
Section: Resultsmentioning
confidence: 66%
“…3 Recent studies on the design and synthesis of oligonucleotides containing thiazole N-oxide disclose that this functionality is unique in the sense of introducing a pronounced directional dipole into molecules that is capable of forming specific and strong hydrogen bonds. 4 Such biologically important findings have triggered intensive efforts aimed at the preparation of the thiazole N-oxide moiety, but the built-in limitations of the orthodox routes used did not result in conspicuous success. The synthesis, via cyclization of v-(dialkylamino-oximinomercapto)acetophenone, involves a multi-step reaction and is restricted to specific starting materials, 5 while direct oxidation using meta-CPBA or permaleic acid requires very long reaction times, leading to thiazole N-oxides in yields of 15 to 50% only.…”
mentioning
confidence: 99%
“…The synthesis, via cyclization of v-(dialkylamino-oximinomercapto)acetophenone, involves a multi-step reaction and is restricted to specific starting materials, 5 while direct oxidation using meta-CPBA or permaleic acid requires very long reaction times, leading to thiazole N-oxides in yields of 15 to 50% only. 3,4,6,7 There is only one example describing the formation of thiazole N-oxide C-nucleoside in good yield using trifluoroacetic anhydride and hydrogen peroxide-urea complex. 4 Clearly, a general and efficient methodology for the preparation of this important family is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation